Suicide in Ireland: the influence of alcohol and unemployment - Walsh, Brendan M.; Walsh, Dermot (Economic & Social Studies, 2011)
We model the behaviour of the Irish suicide rate over the period 1968-2009 using the unemployment rate and the level of alcohol consumption as the principal explanatory variables. We find that alcohol consumption is a significant influence on the suicide rate among younger males. Its influence on the female suicide rate is not well-established, although there is some evidence that it plays a role in the 15-24 age group. The unemployment rate is also a significant influence on the male suicide rate in the younger age groups but evidence of its influence on the female suicide rate is lacking. The behaviour of suicide rates among males aged 55 and over and females aged 25 and over is unaccounted for by our model. The findings suggest that higher alcohol consumption played a significant role in the very rapid increase in suicide mortality among young Irish males between the late 1980s and the end of the century. In the early twenty first century a combination of falling alcohol consumption and low unemployment led to a marked reduction in suicide rates. The recent rise in suicide rates may be attributed to the sharp rise in unemployment, especially among males, but it has been moderated by the continuing fall in alcohol consumption. Finally, we discuss some policy implications of our findings.
Keywords: Young male suicide; Unemployment; Economic sociology; Alcohol consumption